Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/polb.23230
|View full text |Cite
|
Sign up to set email alerts
|

Structure of polymer and particle aggregates in hydrogel composites

Abstract: Knowledge of the structure of a biomaterial is usually vital to control its function. This article provides a structural characterization of a hyaluronan scaffold that has demonstrated good biocompatibility and is used to induce bone regeneration. Hyaluronan hydrogels are appealing materials that can function as a matrix to incorporate both organic and inorganic substances to enhance tissue growth. Because of the intrinsic properties of this swollen matrix, one needs a very sensitive technique that can be appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The investigation of the composite HYH–HAP gel’s microstructure highlighted the influence of HYH particle size and shape and particle size distribution on the gel properties [ 22 , 40 ]. Other investigations showed that gel pore size, porosity, and swelling decreased with increasing HYH concentration [ 41 ].…”
Section: Hyh–hap and Hyh–cap Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of the composite HYH–HAP gel’s microstructure highlighted the influence of HYH particle size and shape and particle size distribution on the gel properties [ 22 , 40 ]. Other investigations showed that gel pore size, porosity, and swelling decreased with increasing HYH concentration [ 41 ].…”
Section: Hyh–hap and Hyh–cap Compositesmentioning
confidence: 99%
“…Due to its unique gel-forming properties, HYH has generated significant interest for the fabrication of composite gels. HYH hydrogels can function as a matrix to incorporate both organic and inorganic substances to enhance tissue growth [ 22 ]. HYH and composites showed interesting biomineralization properties, which are currently under intensive investigation for various applications [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The in-vitro gelling capacity was determined by placing test the freshly prepared solution 0.5 ml of in-situ about quantity timolol hydro which gel in a vial containing freshly prepared simulated tear fluid pH 7.4 and equilibrated at 37ºC. The with temperature visual assessment of gel inspection can also be done for the (Berts et al, 2013).…”
Section: Of Gelling Consistency Eterminationmentioning
confidence: 99%
“…The mechanism of NC in improving mechanical strength is similar to that of rubber reinforcing [21], i.e., by using the surface activity of carbon black particles to adsorb the molecular chains of rubber, forming similar physical crosslinkages so as to play a powerful role in reinforcement and greatly improve its mechanical properties. NCs, depending on the types of nanoparticles, can be divided into the following categories: clay composite hydrogels [22], polymer particle composite hydrogels [23], carbon nanotube reinforced polymer hydrogels [24], and crosslinked polyvinyl alcohol (PVA) nanofiber hydrogels [25].…”
Section: Polymeric Hydrogels With Mechanical Propertiesmentioning
confidence: 99%